Mild leg length discrepancy affects lower limbs, pelvis and trunk biomechanics of individuals with knee osteoarthritis during gait. (October 2016) - Resende, Renan A.; Kirkwood, Renata N.; Deluzio, Kevin J.; Morton, Amy M.; Fonseca, Sérgio T.
Abstract: Background: Leg length discrepancy greater than 1 cm increases odds of progressive knee osteoarthritis in the shorter limb. Methods: Biomechanical data of 15 knee osteoarthritis participants were collected while they walked under two conditions: (1) control — wearing thick sandals; (2) short limb — wearing a thin sandal on the osteoarthritic limb and a thick sandal on the contralateral limb. The thick and thin sandals had 1.45 cm of thickness difference. The knee osteoarthritis limb was analyzed for both conditions. Ankle, knee, hip, pelvis and trunk kinematics and moments were measured with a motion and force capture system. Principal component analysis and mean hypothesis' tests were used to compare the conditions. Findings: The short limb condition reduced rearfoot plantarflexion in loading response and increased plantarflexion in late stance (p < 0.001), increased ankle dorsiflexion moment (p = 0.003), increased knee flexion angle in loading response and delayed knee flexion in late stance (p = 0.001), increased knee extension moment in loading response and increased knee flexion moment in terminal stance (p = 0.023), reduced hip extension moment in early stance and reduced hip flexion moment in late stance (p < 0.001), reduced knee adduction moment (p = 0.015), reduced hip adduction angle (p = 0.001) and moment (p = 0.012) and increased pelvic (p = 0.023) and trunk (p = 0.001) external rotation. Interpretation: Mild leg length discrepancy affects the entire kinetic chain of individuals with knee osteoarthritis during gait, increasing knee sagittal plane loading, which helps to explain why mild leg length discrepancy accelerates knee osteoarthritis progression. Mild leg length discrepancy should not be overlooked in knee osteoarthritis individuals. Highlights: Mild leg discrepancy affects walking biomechanics of knee osteoarthritis patients. Mild leg discrepancy increases sagittal loading of knee osteoarthritis patients. Mild leg discrepancy increases pelvic/trunk rotation of knee osteoarthritis patients. Mild leg length discrepancy should be evaluated in knee osteoarthritis patients.